Scopolamine impairs appetitive but not aversive trace conditioning: role of the medial prefrontal cortex - Pezze, Marie A.; Marshall, Hayley J.; Cassaday, Helen J. (Society for Neuroscience, 2017)
The muscarinic acetylcholine (ACh) receptor is an important modulator of medial prefrontal cortex (mPFC) functions, such as the working memory required to bridge a trace interval in associative leaning. Aversive and appetitive trace conditioning procedures were used to examine the effects of scopolamine (0.1 and 0.5 mg/kg i.p.) in male rats. Follow-up experiments tested the effects of microinfusion of 0.15 μg scopolamine (0.075 μg in 0.5 μL/side) in infralimbic (IL) versus prelimbic (PL) regions of rat mPFC, in appetitive trace and locomotor activity (LMA) procedures. Systemic scopolamine was without effect in an aversive trace conditioning procedure but impaired appetitive conditioning at a 2 s trace interval. This effect was demonstrated as reduced responding during presentations of the conditioned stimulus (CS) as well as during the inter-stimulus-interval (ISI). There was no such effect on responding during food (unconditioned stimulus, US) responding or in the inter-trial-interval (ITI). In contrast, systemic scopolamine dose-relatedly increased LMA. Trace conditioning was similarly impaired at the 2 s trace (shown as reduced responding to the CS and during the ISI, but not during US presentations or in the ITI) after infusion in mPFC, whilst LMA was increased (after infusion in IL only). Thus, results point to the importance of cholinergic modulation in mPFC for trace conditioning and show that the observed effects cannot be attributed to reduced activity.